(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article takes a look at the integration of the video image in contemporary staging, discussing the issue of complexity that this imposes on the modes of presence of the interpreter, the way in which fictional spaces-time intersect and the development of autonomous narrative levels. Starting from the hypothesis that the integration in very high doses of the electronic image in the theatrical representation tends, with different stage directors, to be accompanied by a rarefaction, a disruption and even a near disappearance of the scenic action, the author proposes to examine "effects of absencel0", based on the observation of two German and one Italian productions, carried out between 2002 and 2004: Der Meister und Margarita, staged by Frank Castorf from Bulgakov’s novel; Pablo in der Plusfiliale, a show designed and performed by René Pollesch; and Twin rooms, created by the company Motus.